The Feasibility of GIGANA Comics to Foster Literacy in Students in Disaster Preparedness Schools - Siti Anafiah; Shanta Rezkita (2022)
The purpose of this study was to describe the feasibility of GIGANA comics to foster literacy in students in disaster preparedness schools. This research is RD type. This research phase includes identification problems, planning, development, validation, and product revision. This research produces learning media products in the form of comics GIGANA (Digital Disaster Mitigation). The results of the assessments from media experts and material experts show that indicators of presentation, operation, content, writing, and benefits are appropriate for use in thematic learning for elementary school students.